Alleviation of the effects of saline-alkaline stress on maize seedlings by regulation of active oxygen metabolism by Trichoderma asperellum - Fu, Jian (PLoS One, 2017)
This study investigated the influence of Trichoderma asperellum on active oxygen production in maize seedlings under saline–alkaline stress conditions. Two maize cultivars were tested: ‘Jiangyu 417’ (‘JY417’), which can tolerate saline–alkaline stress; and, ‘Xianyu 335’ (‘XY335’), which is sensitive to saline–alkaline stress. The seedlings were grown on natural saline–alkaline soil (pH 9.30) in plastic pots. To each liter of saline–alkaline soil, 200 mL of T. asperellum spore suspension was applied; three fungal suspensions were used, namely, 1 × 10(3), 1 × 10(6), and 1 × 10(9) spores/L. A control with only the vehicle applied was also established, along with a second control in which untreated meadow soil (pH 8.23) was used. Root and leaf samples were collected when the seedlings had three heart-shaped leaves and the fourth was in the developmental phase. Physical and biochemical parameters related to oxidation resistance were assessed. The results indicated that the ‘JY417’ and ‘XY335’ seedlings showed different degrees of oxidative damage and differences in their antioxidant defense systems under saline–alkaline stress. As the spore density of the fungal suspension increased, the K(+) and Ca(2+) contents in the seedlings increased, but Na(+) content decreased. Moreover, fungal treatment promoted the synthesis or accumulation of osmolytes, which enhanced the water absorbing capacity of the cells, increased antioxidant enzyme activities, enhanced the content of non-enzyme antioxidants, and reduced the accumulation of reactive oxygen species. Fungal treatment alleviated oxidative damage caused by the saline–alkaline stress in roots and leaves of the seedlings. The application of T. asperellum overcame the inhibitory effect of saline–alkaline soil stress on the growth of maize seedlings. In the present experiment, application with 1 × 10(9) spores/L gave the optimal results.